2003
DOI: 10.1124/jpet.102.047050
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Individual Cytochrome P450 Isozymes to theO-Demethylation of the Psychotropic β-Carboline Alkaloids Harmaline and Harmine

Abstract: The psychotropic ␤-carboline alkaloids, showing high affinity for 5-hydroxytryptamine, dopamine, benzodiazepine, and imidazoline receptors and the stimulation of locus coeruleus neurons, are formed endogenously from tryptophan-derived indolealkylamines through the Pictet-Spengler condensation with aldehydes in both plants and mammals. Cytochromes P450 1A1 (18.5), 1A2 (20), and 2D6 (100) catalyzed the O-demethylation of harmaline, and CYP1A1 (98.5), CYP1A2 (35), CYP2C9 (16), CYP2C19 (30), and CYP2D6 (115) catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 44 publications
4
77
0
1
Order By: Relevance
“…1 This is not surprising in light of recent reports describing CYP2D6 activity towards endogenous substrates found in the human brain. 2,3 The CYP2D6 gene locus is highly polymorphic and currently there are 51 allelic variants (CYP2D6*1 to *51 including the ones described within this report) and over 30 additional subvariants defined. 4 As a consequence, CYP2D6 activity ranges widely within a population comprising ultrarapid (UM), extensive (EM), intermediate (IM) and poor (PM) metabolizer phenotypes.…”
Section: Introductionmentioning
confidence: 90%
“…1 This is not surprising in light of recent reports describing CYP2D6 activity towards endogenous substrates found in the human brain. 2,3 The CYP2D6 gene locus is highly polymorphic and currently there are 51 allelic variants (CYP2D6*1 to *51 including the ones described within this report) and over 30 additional subvariants defined. 4 As a consequence, CYP2D6 activity ranges widely within a population comprising ultrarapid (UM), extensive (EM), intermediate (IM) and poor (PM) metabolizer phenotypes.…”
Section: Introductionmentioning
confidence: 90%
“…A previous study reported that the O-demethylation of HM was catalyzed by CYP1A1 (98.5), CYP1A2 (35), CYP2C9 (16), CYP2C19 (30), and CYP2D6 (115), which may exist in the GIT. 24 Degradation in the GIT could be attributed to the first-pass effect and the low oral bioavailability of HM at 25.25%±6.05%. As shown in Figures 9-11, the uptake of HM into Caco-2 cells through passive diffusion mechanism was not dependent on concentration and not affected by energy inhibitors and endocytosis inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Harmane and harmine also exist in various human diets and foodstuff in particularly high ng/g concentrations, such as in espresso coffee brews, alcoholic beverages and cigarette smoke (Anderson et al 2006;Alves et al 2007). Moreover, harmane and harmine endogenously occur in mammalian tissues and body fluids, including the central nervous system (CNS), heart, kidney, liver, brain, adrenal tissue, platelets, plasma and urine (Yu et al 2003). Harmane is highly lipophilic and more easily distributed into brain tissues than peripheral tissues.…”
Section: Harmanementioning
confidence: 99%